(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The water in the Son, Banas, Gopad, gopaldas dam, goriyara dam and Rehi river has longbeen revered for its purity, but recent years have seen a steady decline in quality as a result ofunchecked human activity. In the riparian zones, the physiochemical interactions between the terrestrialand aquatic ecosystems are particularly significant. This article uses a winter and summer of 2022riparian vegetation analysis to assess pollution in the Son, Banas, Gopad, gopaldas dam, goriyara damand Rehi river in Madhya Pradesh (M.P.). The average values of the Simpson’s diversity index (SDI) andthe Shannon-Weiner diversity index (SWDI) were between 0.23 and 0.28, indicating that this part of theSon, Banas, Gopad, gopaldas dam, goriyara dam and Rehi river is in good health. The river is inmoderate health, as shown by the Margalef richness index (MARI) values of 0.49 to 0.52 and the Menhinikrichness index (MERI) values of 0.08 to 0.11. Therefore, numerous indices, including the NationalSocioeconomic Status and Quality Index (NSFWQI), the Composite Tropical Stability Index (CTSI), andthe Stability Index (SDI), have been used to investigate Son, Banas, Gopad, gopaldas dam, goriyara damand Rehi river’s ecological status. The findings demonstrate that ecological well-being is often between a2 and 3. Furthermore, the data show that diversity and richness indices rise from winter to summer,indicating lower pollution levels in the summer. Taking corrective measures to manage the seasonalincrease in pollutants is essential to maintaining excellent water quality throughout the duration.Because of the area’s middling ecological health, the water is unfit for human consumption but suitablefor irrigation, bathing, aquaculture, and life support.